Power and innovation: Excavating pre-1806 steam engines in the Manchester area. (3rd July 2018) - Nevell, Michael
Abstract : This paper reviews the archaeological evidence for the use of stationary steam engines on colliery and textile manufacturing sites in the Manchester city region prior to 1806. It draws upon fieldwork undertaken as a result of developer-funded archaeological work as well as research excavation projects. A series of case studies are used to show the value of excavation in recovering the evidence for early steam technology. In the absence of detailed documentary and above ground structural evidence the recovery of technical information regarding the remains of the steam engines and their associated boilers, and the detailed development of each site, was only possible through archaeological excavation. The paper argues that such excavation work on early mill engine sites and mining pumping engine sites can help in understanding both the development of individual site power systems and the rate of adoption of early steam technology within a particular region.